Ga(DS)3-catalysed double hydroarylation of acetylenic esters with indoles for the synthesis of bisindolyl propanoates. Issue 26 (24th June 2015) - An, Li-Tao; Cai, Jing-Jing; Pan, Xiang-Qiang; Chen, Tang-Ming; Zou, Jian-Ping; Zhang, Wei
Graphical abstract: Abstract: An efficient synthetic method for bisindolyl propanoates has been developed. Ga(DS)3 -catalysed double hydroarylation of acetylenic esters with indoles in water afforded regioselective products with up to 99% yield.